2019
DOI: 10.1080/20008198.2019.1657372
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical correlates of dissociative subtype of posttraumatic stress disorder at an outpatient trauma clinic in South Korea

Abstract: Background: Previous studies on of the dissociative subtype of posttraumatic stress disorder (d-PTSD) have relied on specialized statistical methods (i.e. profile or class analyses) for diagnosis than clinical rating available to clinicians. Objective: This study investigated the prevalence and covariates of d-PTSD diagnosed by a semi-structured interview in a cohort of outpatients with DSM-IV PTSD in a specialized trauma clinic in South Korea. Method: Data from 249 patients with civilian PTSD were examined, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Our PTSD class may represent the dissociative subtype PTSD (APA, 2013), which was also found in a previous LCA study on interpersonal trauma (Palic et al, 2016). Also, a previous Korean sample study found that interpersonal trauma was more associated with dissociative PTSD rather than non-dissociative PTSD (Kim et al, 2019), which supports that our sample is more likely to have a dissociative PTSD.…”
Section: Discussionsupporting
confidence: 83%
“…Our PTSD class may represent the dissociative subtype PTSD (APA, 2013), which was also found in a previous LCA study on interpersonal trauma (Palic et al, 2016). Also, a previous Korean sample study found that interpersonal trauma was more associated with dissociative PTSD rather than non-dissociative PTSD (Kim et al, 2019), which supports that our sample is more likely to have a dissociative PTSD.…”
Section: Discussionsupporting
confidence: 83%
“…However, it is widely recognized that the immediate and long-term mental health consequences of exposure to potentially traumatic life events often extend beyond the symptoms of any single psychological disorder, be it PTSD or otherwise (e.g., Clemens et al, 2018 ; Gribble, Goodwin, & Fear, 2019 ; Hoppen & Morina, 2019 ; Kim et al, 2019 ; McLaughlin, Colich, Rodman, & Weissman, 2020 ; Nordin & Perrin, 2019 ; Pietrzak et al, 2015 ; Sambuco, Bradley, Herring, Hillbrandt, & Lang, 2020 ; Zoellner, Pruitt, Farach, & Jun, 2014 ). Rather, response to traumatic stressors tends to follow the principle of multifinality (Cicchetti & Rogosch, 1996 ) from myriad forms of resilience to psychopathology where similar stressors can lead to various transdiagnostic outcomes across different persons and cultures.…”
mentioning
confidence: 99%
“…Despite these challenges, the current literature signals that dissociation is a potential marker for both BPD severity and poor treatment response, indicating a need to better understand the mechanisms involved and develop strategies to address them. In the PTSD literature, dissociative symptoms are linked to clinical severity and lower response to psychotherapy ( Kim et al, 2019 ; Lanius et al, 2012 ). This reduced response has been explained by data demonstrating prefrontal inhibition of limbic regions, leading to emotional overmodulation in response to emotional or traumatic cues ( Lanius et al, 2010 ; Lyssenko et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%